Thermal upgrading of nickeliferous pyrrhotite tailings: Formation mechanism of ferronickel alloy. (April 2019) - Liu, Feng; Yu, Dawei; Marcuson, Sam; Wang, Fanmao; Li, Bo; Barati, Mansoor
Highlights: High S2 vapor pressure of metal-deficient sulfide contributes to the sulfidization of metallic Fe. The formation of ferronickel particles within pyrrhotite follows an in-situ nucleation and growth mechanism. The formation of ferronickel particles either within newly formed sulfide or at outer edge of residual Fe is a result of cross diffusion of Fe and Ni. Abstract: Current practices of handling pyrrhotite (Pyrr) tailings pose the risk of acid mine drainage (AMD), which is a significant environmental problem. A thermal upgrading process by which nickel value can be recovered in the form of ferronickel alloy is a possible alternative to treat nickeliferous pyrrhotite tailings analyzing 0.5–1.5% Ni. The basis of this process is that the formation of ferronickel alloy from Pyrr is possible at kinetically favorable temperatures once the Fe/S ratio of Pyrr is shifted to stoichiometric or near stoichiometric FeS (troilite) with the addition of iron and/or removal of sulfur under non-oxidizing atmosphere. In this study, the formation mechanism of ferronickel alloy was investigated by treating diffusion couples at 850 °C to better understand the transport phenomena of sulfur, iron and nickel. When a compact of Pyrr powder was coupled with metallic Fe, the ferronickel alloy was found: (1) in the newly-formed sulfide layer adjacent to the remaining metallic Fe; (2) at the outer edge of the remaining metallic Fe; and (3) within the sulfide away from the metal/sulfide interface. The formation mechanism of ferronickel particles in different locations within the diffusion couple was linked to the various mass transport phenomena involved.